2023
DOI: 10.32859/era.26.6.1-72
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of medicinal plants in Surghar Range of Pakistan

Abstract: Background: This comprehensive ethnobotanical study was undertaken for the first time to explore and document the medicinal plants used by the indigenous ethnic communities of Surghar Range, Pakistan. The study area is situated adjacent to Salt Range, which lies on the most southern part of Himalayan Ranges in Pakistan. Despite occurrence of so many medicinal plants, culture history and herbal medicines used among the indigenous communities, no explicit ethnobotanical studies are available from this unique reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Known locally as Mazara, N. ritchieana is beneficial nutritionally and medicinally and is a valuable ethnobotanical resource for making hotpots, brooms, baskets, hand fans, and domestic fuel. Phytochemicals such as flavonoids, alkaloids, and terpenoids can be used to treat diverse types of pathogenic infections (Kumari et al 2016;Rahim et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Known locally as Mazara, N. ritchieana is beneficial nutritionally and medicinally and is a valuable ethnobotanical resource for making hotpots, brooms, baskets, hand fans, and domestic fuel. Phytochemicals such as flavonoids, alkaloids, and terpenoids can be used to treat diverse types of pathogenic infections (Kumari et al 2016;Rahim et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is a comprehensive ethnomedicinal study of the wild edible fruits of the Surghar range, Pakistan. Rahim et al (2023) and Shah et al (2013) have studied the overall flora in the Surghar range, but a recent study focused on wild edible fruits not all plants. So, it is the first-ever ethnomedicinal study of WEFs in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first comprehensive scientific approach to ethnomedicinal studies of wild edible fruits of the Surghar range that is still less explored. Rahim et al (2023) and Shah et al (2013) have studied the overall flora in the Surghar range, but a recent study focused on wild edible fruits, not all plants. They did not focus on fruit species.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional healers use different ingredients such as cow's milk, honey, rice water, cow's urine, ghee, hot water as the medium for herbal drug preparation. These ingredients will enhance and improve the medicinal property of the preparations (Rahim et al 2023, Bhat et al 2019. In this study, 27 monoherbal and 95 polyherbal formulations have been reported in the treatment of neurological disorders (Table 3).…”
Section: Figure 3 Plant Parts Used Versus Number Of Speciesmentioning
confidence: 94%